Personal values and entrepreneurial attitude as intellectual capital: Impact on innovation in small enterprises - Edgar A. Sánchez-Báez; José Fernández Serrano; Isidoro Romero (Amfiteatru Economic Journal, 2018)
This paper analyzes the effects of entrepreneurs' personal values and their entrepreneurial attitudes, as forms of intellectual capital, on the innovative behavior of small businesses. The influence of personal values is examined through Schwartz's value theory and entrepreneurial attitudes via assessments associated with risk taking and personal autonomy. A model of structural equations using the Partial Least Squares technique was applied to a database composed of 191 small business owners in Paraguay. The results show that personal values of conservation and self-enhancement in the entrepreneur have a direct negative effect on innovation. It is also noted that entrepreneurial attitudes, such as openness to change and self-transcendence, have a mediating role in the positive impact of values on innovation. The article contributes to the literature by showing that some elements of intellectual capital, such as entrepreneurial attitudes and entrepreneurs' personal values, interact to influence innovation in small businesses.
Keywords: M14; O30; O54; 330; personal values; entrepreneurial attitude; small business; innovation